Pengembangan Media KPKPD (Kartu Papan Kebutuhan Peserta Didik) Materi Aku dan Kebutuhanku pada IPAS Kelas IV SD Negeri 8 Pangkalanbaru - Selli Agustin; Feri Ardiansah; Hevitria (Universitas Muhammadiyah Bangka Belitung, 2026)
This study is based on a needs analysis of students, which revealed that most students experienced difficulties in understanding the material when relying solely on textbooks. They showed higher motivation to learn through engaging visual media, particularly in the